Seasonal Hunger and Its Mitigation in North-West Bangladesh - Khandker, Shahidur R.; Khalily, M.A. Baqui; Samad, Hussain A. (Taylor and Francis, 2013)
Seasonal hunger may result from seasonality of agriculture when households fail to smooth income and consumption. Using household survey data from the north-west region of Bangladesh, this article examines alternative measures of seasonal hunger, and provides some evidence to support policies and programmes needed to mitigate seasonal hunger. The results suggest that a large majority of food-vulnerable households are the perpetual poor, as opposed to a small percentage of households who are subject to food deprivation only during the lean period. Findings suggest that government safety net programmes and microcredit provide a cushion for the poor to stave off seasonal hunger.